Association of lifestyle behaviours with self-esteem through health-related quality of life in Spanish adolescents - Knox, Emily; Muros Molina, Jose Joaquin (Springer, 2017)
The present research examined the association of Mediterranean diet adherence and physical activity with self- esteem through five components of health-related quality of life. Data were collected from 456 adolescents attending one of five schools in Granada, Spain using a cluster-randomised design. Participants completed questionnaires on Mediterranean diet adherence, physical activity, self-esteem and health-related quality of life (HRQoL). Models were constructed to identify associations between Mediterranean diet adherence and physical activity on self-esteem. Mediational analysis using bootstrapped confidence intervals examined possible mediation by five components of HRQoL. Mediterranean diet adherence and physical activity engagement were associated with four components of HRQoL: more positive physical wellbeing, psychological wellbeing, family relationships and autonomy support and perceptions of the school environment. Both lifestyle behaviours were positively associated with self-esteem. Both relationships were mediated through positive psychological wellbeing and perceptions of the school environment. Physical wellbeing was also a mediator of the relationship between physical activity and self-esteem.